Dynamics of consumer inflation with irrational expectations and exogenous economic shocks - Gerunov, Anton A. (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: Economic modelling has long relied on the assumption of individual rationality. Advances in the behavioural sciences and the problematic empirical fit of rational models have made this central assumption increasingly untenable. The article proposes an alternative and more realistic approach to model agents as forming diverse expectations. Methodology: The study leverages the approach of heterogeneous expectations and shows how to formally incorporate behavioural heuristics into the expectations formation process. It presents the setup and computation of a small dynamic stochastic general equilibrium (DSGE) model, based on heterogeneous expectations and compares its dynamics to the rational expectations benchmark. Results: The DSGE model shows that an economy with heterogeneous expectations generates business cycles of its own through the mechanism of self-fulfilling prophecies. As agents’ expectations diverge from rationality, the economy drifts away from its potential output and extreme inflation episodes ensue. A comparison with empirical data from the European Union serves to further corroborate and validate model insights. Implications and recommendations: This outcome underlines the importance of sentiments as drivers of price dynamics and proposes a viable alternative for modelling them. The results show the importance of complementing current mainstream modelling with more psychological insights on the microfoundations of agent behaviour to better approximate the workings of the economic system. Originality/value: The paper shows how alternative expectations formation mechanisms can be incorporated into a small DSGE model, and provides a simple but realistic way to formal model herding and validates its results through a comparison with actual statistical data from the European Union.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 112-132
Keywords: macroeconomic model; inflation; prices; simulation; heterogeneous expectations; DSGE; behavioural macroeconomics